Embracing Community Ecology in Plant Microbiome Research. (June 2018) - Dini-Andreote, Francisco; Raaijmakers, Jos M.
Abstract : Community assembly is mediated by selection, dispersal, drift, and speciation. Environmental selection is mostly used to date to explain patterns in plant microbiome assembly, whereas the influence of the other processes remains largely elusive. Recent studies highlight that adopting community ecology concepts provides a mechanistic framework for plant microbiome research.